"d‐Electron Complementation" Induced V‐Co Phosphide for Efficient Overall Water Splitting (Adv. Energy Mater. 38/2021). Issue 38 (14th October 2021) - Zhang, Rui; Wei, Zhenhua; Ye, Gaoyang; Chen, Guanjie; Miao, Jiaojiao; Zhou, Xuehua; Zhu, Xiangwei; Cao, Xiaoqun; Sun, Xiangnan
Abstract : Water Splitting In article number 2101758, Rui Zhang, Xiangwei Zhu, Xiaoqun Cao, Xiangnan Sun, and co‐workers report a Co‐V phosphide nanoneedle electrocatalyst for efficient overall water splitting, which stems from the "d‐electron complementation" effect from V to Co in the matrix. This highlights d‐orbital engineering in developing novel efficient bifunctional electrocatalysts.